Avaliação da taxa de sobrevivência e da condição peri-implantar em pacientes periodontalmente comprometidos : estudo transversal de implantes em função por um período de 10 a 18 Anos - Lopes, Guilherme da Rocha Scalzer (2017)
Despite high survival rate of dental implants, the peri-implant region can show a inflammatory lesion known as peri-implant mucositis, which when it is not treated can result in peri-implantitis. These diseases are inflammations induced by biofilm as similar as to the etiopathogenesis of periodontal diseases. Thus, the aim of this study was to evaluate the survival rate of dental implants and the profile of peri-implant tissues in periodontally compromised patients, whereas they could be more susceptible to peri-implant diseases. 58 implants were evaluated, clinically and radiographically, installed in seven individuals treated by the same team of professionals, during the years 1997 and 2005 in a private dental clinic in Vitória (city) / Brazil. At that time of data collection, all implants were at least 10 years of functional loading. The variables related to the dental implants evaluated were: visible plaque index (VPI), gingival index (GI), probing depth (PD), bleeding on probing (BOP) and bone level attachment (BL), in order to relate them to the survival rate and the classification of dental implants. The results showed a survival rate of 100% and the total of 58 implants were classified: 11 (18.9%) as healthy and 12 (20.7%) as clinically stable. The other 35 implants (60.4%) had some type of peri-implant inflammation, 20 of them (34.5%) were diagnosed with peri-implant mucositis and 15 (25.9%) with peri-implantitis. Among the variables studied, the results showed statistically significant differences in the implant location (p<0.01) and in the gingival index (GI) (p = 0.03). Most implants placed in the maxilla (85.7%) were classified with some type of peri-implant disease (mucositis or periimplantitis). For the implants which resulted in score 1 for ISGM, most of it (75.0%) were also classified with some type of peri-implant inflammation (mucositis or periimplantitis). This study concluded that implants placed in periodontally compromised patients may have high long-term survival rates. However, even with this high survival rate, most implants were classified with some type of peri-implant inflammation.